2011
DOI: 10.2528/pier11030603
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Channel SPCMB-Tops Sar for High-Resolution Wide-Swath Imaging

Abstract: Abstract-To improve the impaired azimuth resolution of the novel Terrain Observation by Progressive Scans (TOPS) mode, a new multichannel single phase center multiple beam (SPCMB) TOPS mode is proposed in this paper for high-resolution wide-swath (HRWS) imaging. However, the progressive azimuth beam scanning leads to the Doppler spectrum aliasing and both beam center time and Doppler centroid varying with the target's azimuth location. Challenges may arise for processing the SPCMB-TOPS SAR data from these prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…With the rapid development in the past years [1][2][3][4][5], the high-resolution SAR is capable of producing very high quality images. It is reported that typical sensor platforms is able to provide wide area search coverage (approximately 100 km 2 area per minute) at 1.0 m × 1.0 m resolution [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development in the past years [1][2][3][4][5], the high-resolution SAR is capable of producing very high quality images. It is reported that typical sensor platforms is able to provide wide area search coverage (approximately 100 km 2 area per minute) at 1.0 m × 1.0 m resolution [6].…”
Section: Introductionmentioning
confidence: 99%
“…It receives the raw echoes of radar signals and provides the high resolution SAR imagery by complex imaging process [1]. Usually, SAR transmits the Chirp Scaling pulses and receives the backscatter echoes in broadside mode which the SAR antenna is pointed 90 • with respect to the velocity vector of the platform.…”
Section: Introductionmentioning
confidence: 99%
“…Primary studies have demonstrated the potential advantages to simultaneously improve the performance of wide swath Synthetic Aperture Radar (SAR) imaging and ground moving target detection by utilizing multiple antennas both at transmission and reception [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%